The Influence of Capital Structure and Profitability on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange - Prasetyo, Muhammad Fajri (Global Sustainability Research Institute, 2026)
This study aims to analyze the effect of capital structure and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research approach used is quantitative with a causality design. The research data are secondary data obtained from the companies' annual financial reports, using purposive sampling, resulting in 60 company-year observations. Capital structure is proxied by the Debt to Equity Ratio (DER), profitability is proxied by Return on Assets (ROA), and firm value is proxied by Price to Book Value (PBV). The analytical methods used include descriptive statistical analysis, classical assumption tests, and multiple linear regression analysis. The results show that capital structure has a negative and significant effect on firm value, indicating that excessive use of debt can increase financial risk and undermine investor perceptions. Meanwhile, profitability has a positive and significant effect on firm value, indicating that a company's ability to generate profits is a major factor in increasing firm value in the market. Simultaneously, capital structure and profitability have a significant effect on firm value. The findings of this study imply that companies need to optimally manage funding policies and improve profitability performance to maximize firm value. This research is expected to provide empirical contributions to the development of financial management literature and provide considerations for company management and investors in financial decision-making.